Electrochemical characterization of supercapacitors based on carbons derived from coffee shells - Jisha, M.R.; Hwang, Yun Ju; Shin, Jae Sun; Nahm, Kee Suk; Prem Kumar, T.; Karthikeyan, K.; Dhanikaivelu, N.; Kalpana, D.; Renganathan, N.G.; Stephan, A. Manuel (Materials chemistry and physics, 2009)
Carbons derived by pyrolysis of coffee shells treated with ZnCl 2 were used as electrode materials in symmetric electrochemical supercapacitors. Scanning electron microscopy showed that the carbon from the porogen-free shells show a flake-like structure, while those from the ZnCl 2-treated coffee shells have a loose, disjointed structure with no definite shape. X-ray diffraction studies indicated the presence of small domains of coherent and parallel stacking of the graphene sheets. The average surface area of the carbon was 842 m 2 g −1, with an average micropore area of 400 m 2 g −1. Cyclic voltammetric studies suggested a specific capacitance of about 150 F g −1. Self-discharge studies on the devices showed a large retention time.